Artificial Intelligence in Education. Posters and Late Breaking Results, Workshops and Tutorials, Industry and Innovation Tracks, Practitioners, Doctoral Consortium and Blue Sky 25th International Conference, AIED 2024, Recife, Brazil, July 8-12, 2024, Proceedings, Part I - Olney, Andrew M.; Chounta, Irene-Angelica.; Liu, Zitao; Santos, Olga C.; Bittencourt, Ig Ibert; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This volume constitutes poster papers and late breaking results presented during the 25th International Conference on Artificial Intelligence in Education, AIED 2024, which took place in Recife, Brazil, during July 8-12, 2024. The 18 full papers and 92 short papers were carefully reviewed and selected from 200 submissions. They are organized in topical sections as follows: Part One: Blue Sky, Industry, Innovation and Practitioner, WideAIED and Late-Breaking Results. Part Two: Late-Breaking Results, Doctoral Consortium, Workshops and Tutorials.
-- Blue Sky. -- Aligning AIED Systems to Embodied Cognition and Learning Theories. -- Ethical AIED and AIED Ethics: Toward Synergy Between AIED Research and Ethical Frameworks. -- Enhancing LLM-Based Feedback: Insights from Intelligent Tutoring Systems and the Learning Sciences. -- Flowing through Virtual Realms: Leveraging Artificial Intelligence for Immersive Educational Environments. -- Industry, Innovation and Practitioner. -- The Impact of Example Selection in Few-shot Prompting on Automated Essay Scoring Using GPT Models. -- Bringing AIED, Public Policy and GDPR To Promote Educational Opportunities in Brazil. -- Towards Explainable Authorship Verification: An Approach to Minimise Academic Misconduct in Higher Education. -- AI in K-12 Social Studies Education: A Critical Examination of Ethical and Practical Challenges. -- Enhancing Programming Education with ChatGPT: A Case Study on Student Perceptions and Interactions in a Python Course. -- LANSE: A cloud-powered learning analytics platform for the automated identification of students at risk in learning management systems. -- Parsing Post-Deployment Students' Feedback: Towards a StudentCentered Intelligent Monitoring System to Support Self-Regulated Learning. -- How Do Strategies for Using ChatGPT Affect Knowledge Comprehension?. -- Automatic Lesson Plan Generation via Large Language Models with Self-Critique Prompting. -- Systematic Needs Analysis of Advanced Digital Skills for Postgraduate Computing Education: The DIGITAL4Business Case. -- WideAIED. -- Predictive Model of School Dropout Based on Undergraduate Course Self-Assessment Data. -- Expectations of higher education teachers regarding the use of AI in education. -- Brilla AI: AI Contestant for the National Science and Maths Quiz. -- Exploring NLP and Embedding for Automatic Essay Scoring in the Portuguese. -- Enhancing General Reading Understanding: measuring foundational reading skills relevance. -- Gendered Responses to AI Governance: Insights from a Quantitative National Survey on ChatGPT Usage Among Students and Educators. -- Global trends in scientific debates on trustworthy and ethical Artificial Intelligence and education. -- ChatGPT-based Virtual Standardized Patient that Amends Overly Detailed Responses in Objective Structured Clinical Examinations. -- Contextual Features for Automatic Essay Scoring in Portuguese. -- Breaking the Cycle: AI Boosting Communication Skills of Low-Income Students in Brazil. -- Late-Breaking Results. -- Towards Human-like Educational Question Generation with Small Language Models. -- Large Language Models for Career Readiness Prediction. -- Difficulty-Controllable Multiple-Choice Question Generation for Reading Comprehension Using Item Response Theory. -- Can VLM Understand Children's Handwriting? An Analysis on Handwritten Mathematical Equation Recognition. -- To Kill a Student's Disengagement: Personalized Engagement Detection in Facial Video. -- Automated Detection and Analysis of Gaming the System in Novice Programmers. -- Implementation and evaluation of impact on student learning of an automated platform to score and provide feedback on constructed-response problems in chemistry. -- An Interpretable Approach to Identify Performance Indicators within Unstructured Learning Environments. -- Masked Autoencoder Transformer for Missing Data Imputation of PISA. -- Effective and Scalable Math Support: Experimental Evidence on the Impact of an AI-Math Tutor in Ghana. -- Interpret3C: Interpretable Student Clustering Through Individualized Feature Selection. -- Recurrent Neural Collaborative Filtering for Knowledge Tracing. -- EDEN: Enhanced Database Expansion in eLearning: A Method for Automated Generation of Academic Videos. -- Automatic Short-Answer Grading in College Mathematics Using In-context Meta-learning: An Evaluation of the Transferability of Findings. -- Enhancing Algorithmic Fairness in Student Performance Prediction through Unbiased and Equitable Machine Learning Models. -- Leveraging GPT-4 for Accuracy in Education: A Comparative Study on Retrieval-Augmented Generation in MOOCs. -- A Personalized Multi-region Perception Network for Learner Facial Expression Recognition in Online Learning. -- Neural Automated Essay Scoring for Improved Confidence Estimation and Score Prediction through Integrated Classification and Regression. -- An Intelligent System for Chinese Dance Creation using Generative Artificial Intelligence. -- Leveraging Language Models and Audio-Driven Dynamic Facial Motion Synthesis: A New Paradigm in AI-Driven Interview Training. -- Potential Pitfalls of False Positives. -- Predictive Modelling with the Open University Learning Analytics Dataset (OULAD): A Systematic Literature Review. -- GAMAI, an AI-powered Programming Exercise Gamifier tool. -- Generating Contextualized Mathematics Multiple-Choice Questions Utilizing Large Language Models. -- Generative AI in K-12: Opportunities for Learning and Utility for Teachers.
Keywords: Artificial intelligence; Database management; Data mining; Social sciences -- Data processing; User interfaces (Computer systems).; Human-computer interaction; Education -- Data processing; Artificial Intelligence; Database Management; Data Mining and Knowledge Discovery; Computer Application in Social and Behavioral Sciences; User Interfaces and Human Computer Interaction; Computers and Education